2020
DOI: 10.3390/en13184729
|View full text |Cite
|
Sign up to set email alerts
|

Application of Waveform Stacking Methods for Seismic Location at Multiple Scales

Abstract: Seismic source location specifies the spatial and temporal coordinates of seismic sources and lays the foundation for advanced seismic monitoring at all scales. In this work, we firstly introduce the principles of diffraction stacking (DS) and cross-correlation stacking (CCS) for seismic location. The DS method utilizes the travel time from the source to receivers, while the CCS method considers the differential travel time from pairwise receivers to the source. Then, applications with three field datasets ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Several recent studies have shown the suitability of the array for analyzing the spatiotemporal clustering of seismicity (Cochran et al, 2020), source spectral properties (Kemna et al, 2020), near-source radiation patterns (Trugman et al, 2021), and the leaking modes from ambient noise (Zhengbo . Two events from the OGS catalog beneath the array have already been used to demonstrate the effectiveness of DS-based seismic location methods at regional scale (Lei Li, Xie, et al, 2020).…”
Section: Datasetmentioning
confidence: 99%
“…Several recent studies have shown the suitability of the array for analyzing the spatiotemporal clustering of seismicity (Cochran et al, 2020), source spectral properties (Kemna et al, 2020), near-source radiation patterns (Trugman et al, 2021), and the leaking modes from ambient noise (Zhengbo . Two events from the OGS catalog beneath the array have already been used to demonstrate the effectiveness of DS-based seismic location methods at regional scale (Lei Li, Xie, et al, 2020).…”
Section: Datasetmentioning
confidence: 99%
“…Energies 2022, 15, 2772 2 of 15 absolute values, squared amplitudes, envelopes, and their extended characteristic functions [6,7]. For instance, Kao and Shan, and Liao et al, presented the source scanning algorithm (SSA) and its improved method by introducing the weighting factor based on absolute values of the amplitudes, respectively [8,9].…”
Section: Introductionmentioning
confidence: 99%